Penyuluhan tentang Anemia pada Remaja - Sri Maharani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Anemia is a nutritional problem in the world which occurs not only in developing countries but also in developed countries. Low iron intake often occurs in people who consume foods that are less diverse, such as protein. Iron deficiency anemia is more common in young women than young men because young women experience menstruation every month and are in their infancy, thus requiring more iron intake. The problems faced by partners today include the lack of knowledge about adolescents about anemia, so it is considered necessary to provide counseling to provide knowledge to adolescents to prevent anemia in adolescents. Community Service Activities are carried out at SMP N 13 Jambi City. The time of implementation is in April 2018. The target is students of SMP N 13 Kota Jambi. Community service methods survey approach, lecture, discussion, demonstration / simulation. The results obtained are students able to understand about the prevention of anemia in adolescents. It is recommended that health workers, especially at the Puskesmas, give more counseling about anemia to young women before giving blood-added tablets, so that students get information about anemia and want to consume the added blood tablets.